Chiral Pyrophosphoric Acid Catalysts for the para-Selective and Enantioselective Aza-Friedel–Crafts Reaction of Phenols - Okamoto, Haruka; Toh, Kohei; Mochizuki, Takuya; Nakatsuji, Hidefumi; Sakakura, Akira; Hatano, Manabu; Ishihara, Kazuaki (Synthesis, 2018)
Chiral BINOL-derived pyrophosphoric acid catalysts were developed and used for the regio- and enantioselective aza-Friedel–Crafts reaction of phenols with aldimines. ortho/para-Directing phenols could react at the para-position selectively with moderate to good enantioselectivities. Moreover, the gram-scale transformation of a product into the key intermediate for the antifungal agent (R)-bifonazole was demonstrated.
Keywords: Brønsted acid; phosphoric acid; pyrophosphoric acid; organocatalyst; aza-Friedel–Crafts reaction; phenol; regio-selectivity